Comparison of Reference Heights of O/N2 and ∑O/N2 Based on GUVI Dayside Limb Measurement - Tingting Yu; Zhipeng Ren; You Yu; Xinan Yue; Xu Zhou; Weixing Wan (Space Weather)
Abstract We define a new thermospheric concept, the reference heights of O/N2, referring to a series of thermospheric heights corresponding to the fixed ratios of O to N2 number density. Here, based on Global Ultraviolet Imager (GUVI) limb measurement, we compare O/N2 column density ratio (∑O/N2) and the reference heights of O/N2. We choose the transition height of O and N2 (transition height hereafter), a special reference height at which O number density is equal to N2 number density, to verify the connection with ∑O/N2 during geomagnetically quiet periods. It is found that transition height and ∑O/N2 have noticeable negative correlation with correlation coefficient of ‐0.887. An empirical model of transition height (O/N2 model hereafter) is established based on nonlinear least‐squares‐fitting method. The considerable correlation (greater than 0.96), insignificant errors (less than 4%) and the great influencing weight of ∑O/N2 to reference heights indicate the validity of O/N2 model and the existence of quantitative relation between ∑O/N2 and transition height. Besides, it is verified that the similar quantitative relation also exists between ∑O/N2 and reference heights of other O/N2 values. Namely, using the O/N2 model coefficients, we can roughly get the whole altitude profiles of O/N2 within 6% precision for any given ∑O/N2.